EARNED VALUE ANALYSIS FOR AIRCRAFT MANUFACTURING PROJECTS (The Indonesian Journal of Business Administration, 2019)
Indonesian Aerospace is engaged in the manufacture and sale of Aircraft and Helicopters and Services. Timely, precise costing and project accuracy are the key success factors to be considered in aircraft manufacturing project to measure both efficiency and effectiveness in the use of resources in the aircraft manufacturing project.At this time, the problem of on-time delivery has been the main issue in the aircraft delivery at IAe, so it needs a more precise method and accurate which can measure the performance status to predict more accurate result of project in future. In variance method the project cost monitoring and control, display comparisons between planned cost and actual and each other is controlled separately (cost, schedule, and performance). The variance method potentially creates burdens in evaluating project’s progression and forecasting of both schedule and cost performance at completion. This research focuses on eliminating those issues through implementation of Earned Value Management (EVM) method as part of Project Management Body of Knowledge (PMBOK).In EVM method can combine three dimensions, which are scheduled, cost and work performance so that it can be estimated the cost and time to complete the project. The ultimate benefits will be improvement on cost efficiency and on-time delivery of the aircraft manufacturing. Keywords: Variance Method, EVM, Aircraft manufacturing projects, PMBOK, delayed on delivery